EDUKASI REMAJA MELALUI KEGIATAN PENYULUHAN MENGENAI IMUNITAS TUBUH DAN PEMERIKSAAN HEPATITIS - GUSTIADI SAPUTRA; SIGIT MARIYANTO; FINA FISABILILLAH; EGITA WINDRIANATAMA PUSPA (Jurnal SADEWA, 2025)
Hepatitis is an inflammation of liver cells that is often caused by infections (viruses, bacteria, parasites), consumption of drugs, obesity, and autoimmune diseases. This inflammation can worsen from acute to chronic inflammation of the liver. The course of hepatitis B disease can be divided into several phases, including the incubation period, acute phase, aggregation window period, and recovery period. Each stage has a certain duration and different clinical symptoms in patients, as well as serological features that can be used to determine the stage a person is in. Transmission of the hepatitis virus through percutaneous and mucous membranes infected by blood, semen, vaginal secretions and saliva. In extreme cases, hepatitis B can survive for more than a week on dry surfaces, thus increasing cases of transmission within a family. One way to prevent this Hepatitis disease is to do early examination or screening for teenagers in schools, against this disease, using HbsAg examination (immunochromatography/ICT method). And the results of the HbsAg screening test at this school on 25 students, all the results were non-reactive (-). So it can be concluded that none of the teenagers examined were infected with Hepatitis